Etude de cas : la bipédie des chimpanzés de la communauté de Sebitoli, Ouganda - Lise Pernel; Brigitte Senut; Dominique Gommery; John Paul Okimat; Edward Asalu; Sabrina Krief (Revue de Primatologie)
To better understand the selective pressures associated with the emergence of bipedal behaviours in the human lineage, the study of bipedal behaviours and their context in modern chimpanzees (Pan troglodytes) provides some basis for comparison. Bipedalism in chimpanzees in the wild and a chimpanzee living with humans were studied to achieve this. In the wild population, the adoption of bipedal behaviours enables chimpanzees to stand up to detect possible threats, free their hands for carrying objects, extract food that is difficult to access, or parade. Using videos from presence detection cameras set up in Sebitoli, Kibale National Park, Uganda, the bipedal behaviours adopted by wild chimpanzees were researched and analysed to study their contexts. In addition, the bipedalism of a 4-year-old orphaned juvenile male chimpanzee rescued and raised by humans was studied using video. Wild chimpanzees exhibited bipedal behaviours in 35 out of the 1451 videos recordings. Ten instances were related to vigilant postures at the edge of their forest habitat where there are cornfields guarded by farmers and 18 show bipedal behaviours associated with foraging for honey using stick-like tools. This method detected few records of charging (3) or carrying food (2). In contrast, most (11) of the orphan chimpanzee's bipedal behaviours involved carrying or handling objects. The study of bipedalism in wild individuals and the orphaned individual (male juvenile) showed that the orphaned juvenile had a higher average number of steps (13.9 vs 2 steps) and duration of bipedalism (5.5 vs 3 seconds) than wild chimpanzees.